2021
DOI: 10.3389/fonc.2021.745657
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Prostate MRI in Biopsy-Naïve Men: A Prospective Evaluation of Performance and Biopsy Strategies

Abstract: ObjectivesThis study aims to prospectively estimate the diagnostic performance of multiparametric prostate MRI (mpMRI) and compare the detection rates of prostate cancer using cognitive targeted transrectal ultrasound (TRUS) guided biopsies, targeted MR-guided in-bore biopsies (MRGB), or both methods combined in biopsy-naïve men.MethodsThe biopsy-naïve men referred for mpMRI (including T2-weighted, diffusion-weighted and dynamic contrast enhanced MRI) due to prostate cancer suspicion (elevated prostate-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…According to a study by Natale et al, PSAD is a useful tool that can be consulted to determine whether a biopsy in patients with PI-RADS3 is required. [ 32 ]. Zhang et al also reported that PSAD could improve the detection of PCa, as well as csPCa, for PI-RADSv2 score-3 lesions [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Natale et al, PSAD is a useful tool that can be consulted to determine whether a biopsy in patients with PI-RADS3 is required. [ 32 ]. Zhang et al also reported that PSAD could improve the detection of PCa, as well as csPCa, for PI-RADSv2 score-3 lesions [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The in-house collected dataset was obtained from St. Olavs Hospital, Trondheim University Hospital, Trondheim, Norway between March 2015 and December 2017 as part of a previous prospective study [ 12 ]. It consists of mpMR images from 233 patients (median age = 65; range: 44–76 years) who were examined due to suspicion of prostate cancer, via the Norwegian standardized care pathway, in which patients with elevated PSA and/or abnormal digital rectal exam results are referred for an initial mpMRI scan to identify suspicious cancerous tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, many efforts have been made to identify new biomarkers that could improve PCa detection. PSA density (PSAD) is a clinically useful tool to compensate for the low sensitivity of PSA, and recent studies have reported that PSAD is effective in determining whether to perform a prostate biopsy and improves the detection of PCa and clinically significant PCa (csPCa) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%